Pembentukan Brand Image Elzatta Hijab Pt Bersama Zatta Jaya (Elcorps) - Noviko, Angela Gaya; Rosyidi, Imron (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the description of the process of forming the Elzatta Hijab brand image carried out by Elcorps based on the theoretical basis of Hermawan Kartajaya, namely the PDB (positioning, differentiation , brand). Triangle Model which is relevant to the research phenomenon. This research uses descriptive qualitative research methods with data collection techniques, namely passive participant observation and in-depth interviews. The results of this study explain that the formation of the Elzatta Hijab brand image is in accordance with the three elements in the PDB Triangle Model. (1) positioning, namely attracting influencers who are viral and establishing good relations with the muslimah community. (2) differentiation , namely, first conducting a SWOT analysis with the store as the strength aspect, secondly marketing products online through KOL, public figures, and communities to increase sales, thirdly becoming a pioneer of quality muslim brand motifs in Indonesia, and fourthly packaging interesting content according to product occasion. (3) brand, namely placing the brand logo on products and related content, doing three sixty marketing in shaping brand strength , and finally taking an emotional and social approach with customers and members. The impact of this research is that companies can gain insights into the strategy for forming the Elzatta Hijab brand image.